META ANALYSIS OF THE EFFECT OF THE USE OF VIDEO ON STUDENT LEARNING OUTCOMES IN PHYSICS AND SCIENCE LESSONS - Diffa Azilia; Yenni Darvina; . Desnita; . Murtiani; Rahmi Zulva (Universitas Negeri Padang, 2022)
Physics is a subject that examines the phenomena that exist in the universe. Not all of the physics and science materials studied can be visualized because not all of them are concrete. This makes it difficult for students to understand the physics and science material. The solution that fits this problem is to apply the use of video to the students' physics and science learning process. The application of video in learning is expected to be able to improve student learning outcomes. Research on the use of video has been done by many previous researchers. The results of this study indicate that there is a positive influence from the use of video on student learning outcomes.This research method uses a meta-analysis method by collecting 26 articles published in 2014-2021. The article consists of 24 national articles and 2 international articles. The selected articles are articles that can be obtained the effect size on the application of learning videos in physics and science lessons. The effect size value obtained is then grouped into three indicators, namely based on education level, research area, and learning model.Based on this research, it can be concluded that: (1) Effect size on the effect of using video based on indicators of education level, obtained very high criteria for junior high school level, (2) Effect size on the effect of using video when compared based on the indicators of the research area, obtained high criteria for the South Sulawesi region, (3) Effect size on the effect of using video when compared based on the learning model, obtpained high criteria for the Creative Problem Solving learning model.